Pemberdayaan Perempuan Pengerajin Industri Minyak Kelapa Tandusan Di Desa Bebandem Karangasem - Dian Tariningsih; Luh Kadek Budi Martiningsih; Ni Wayan Arni Sardi; I Wayan Wesna Astara (Denpasar Institute, 2021)
Bebandem village has a vision as a trade and service center supported by the potential of agriculture and community industry, facing the problem of low income, so that efforts are needed to empower the community. The purpose of writing this paper is to determine the impact of empowering women craftsmen on the productivity of the coconut oil industry Bebandem Village, Karangasem. The methods used are training and mentoring. The empowerment results found an increase in knowledge, infrastructure and facilities such as a coconut grater machine, a coconut squeezer and an increase in the productivity of women craftsmen in the coconut oil industry